Kepemimpinan Kepala Sekolah dan Kinerja Guru dalam Meningkatkan Mutu Pembelajaran SD Negeri 26 Muara Sugihan - Mamik Harisanti; Syaiful Eddy; Muhammad Fahmi (CV. Ulil Albab Corp, 2026)
This study aims to explain: (1) the quality of the principal’s leadership at SD Negeri 26 Muara Sugihan; (2) the performance of teachers at SD Negeri 26 Muara Sugihan; and (3) strategies for improving learning quality through the principal’s leadership and teacher performance. This research employed a qualitative approach with a descriptive method. The study was conducted at SD Negeri 26 Muara Sugihan, involving seven informants. Data were collected through interviews, observations, and documentation. The findings indicate that the principal’s leadership quality has a significant influence on teacher performance and learning quality. The principal demonstrates communicative and adaptive leadership characteristics and is capable of supporting the implementation of contextual curricula. In addition, the principal is proactive in providing coaching and professional development. This leadership quality serves as a key factor in creating a conducive learning environment. The study also found that teacher performance is in an improving phase; teachers have begun to apply varied teaching methods and integrate technology, although the implementation is not yet evenly distributed due to capacity limitations, administrative demands, and inadequate facilities. The principal’s role in supervision, mentoring, and professional support is identified as a driving factor in enhancing teacher performance. Furthermore, improving learning quality is carried out through continuous coaching, exemplary leadership, strengthened collaboration, innovation, and emotional and technical support. Teachers perceive that the leadership applied is open and provides space for professional growth. With a combination of enhanced teacher competence, improved facilities, and continuous evaluation, the learning quality at SD Negeri 26 Muara Sugihan has the potential to continue improving.